Well-posedness cho bài toán bất đẳng thức tựa biến phân - Vũ, Hồng Trinh (Trường Đại học Đà Lạt, 2012)
In this paper, we consider sufficient condition of well-posedness of the approximate solotion sets for quasivariational inequalities problem